Comparison Performances of Indirect Field Oriented Control for Three-Phase Induction Motor Drives - Hasif Aziri; Fizatul Aini Patakor; Marizan Sulaiman; Zulhisyam Salleh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper presents the comparative performances of Indirect Field Oriented Control (IFOC) for the three-phase induction motor. Recently, the interest of widely used the induction motor at industries because of reliability, ruggedness and almost free in maintenance. Thus, the IFOC scheme is employed to control the speed of induction motor. Therefore, P and PI controllers based on IFOC approach are analyzed at differences speed commands with no load condition. On the other hand, the PI controller is tuned based on Ziegler-Nichols method by using PSIM software which is user-friendly for simulations, design and analysis of motor drive, control loop and the power converter in power electronics studies. Subsequently, the simulated of P controller results are compared with the simulated of PI controller results at difference speed commands with no load condition. Finally, the simulated results of speed controllers are compared with the experimental results in order to explore the performances of speed responses by using IFOC scheme for three-phase induction motor drives.